en - Candra Gunasari, Ni Putu (e-Journal of Linguistics; Vol 15 No 1 (2021): ejl-January, 2020)
This research aims to analyze cohesion are considered as two important components of writing skills which are an important part of writing quality assurance. This research was conducted in several public high schools in Denpasar. This study took class X senior high school because the curriculum in class X senior high school included learning to write narrative. The results of this study are related to the three existing problem formulations. The discussion of the results of this research is in the form of the first one related to the implementation of comic media without text in learning to write narrative in class X Denpasar State Senior High School, the cohesion aspect of learning to write narration using comic media without text in class X senior high school Negeri Denpasar.